Characterization of ictal slow waves in epileptic spasmsCharacterization of ictal slow waves in epileptic spasms. Issue 4 (25th January 2016) - Honda, Ryoko; Saito, Yoshiaki; Okumura, Akihisa; Abe, Shinpei; Saito, Takashi; Nakagawa, Eiji; Sugai, Kenji; Sasaki, Masayuki
Abstract: We characterized the clinico‐neurophysiological features of epileptic spasms, particularly focusing on high‐voltage slow waves during ictal EEG. We studied 22 patients with epileptic spasms recorded during digital video‐scalp EEG, including five individuals who still had persistent spasms after callosotomy. We analysed the duration, amplitude, latency to onset of electromyographic bursts, and distribution of the highest positive and negative peaks of slow waves in 352 spasms. High‐voltage positive slow waves preceded the identifiable muscle contractions of spasms. The mean duration of these positive waves was 569±228 m, and the mean latency to electromyographic onset was 182±127 m. These parameters varied markedly even within a patient. The highest peak of the positive component was distributed in variable regions, which was not consistent with the location of lesions on MRI. The peak of the negative component following the positivity was distributed in the neighbouring or opposite areas of the positive peak distribution. No changes were evident in the pre‐ or post‐surgical distributions of the positive peak, or in the interhemispheric delay between both hemispheres, in individuals with callosotomy. Our data imply that ictal positive slow waves are the most common EEG changes during spasms associated with a massive motor component. Plausible explanations for these widespread positive slow waves include the notion that EEG changes possibly reflect involvement of both cortical and subcortical structures.